Structural change and economic policy in Israel - Pack, Howard (New Haven : Yale University Press, 1971)
This book is on the structural changes and economy policy in Israel
Includes index.
Includes bibliographical references: p. 261-268.
oo 27/08/2018
Loans
Keywords: Economic situation; Israel